Comparison of professional self esteem of public and private school mathematics teachers in Ibadan metropolis, Oyo State (2018)
Professional self-esteem is the appraisal of one’s cognitive, emotional and behavioural capabilities that makes an individual a true professional in real sense. It is to get to know the real essence of a profession, its perquisite along and competencies of a professional. Professional self-esteem of mathematics teachers varied across the level and location of operations of mathematics teachers especially between public and private primary school in Ibadan metropolis, Nigeria evidenced from reports. This study, therefore, investigated the comparison of public and private junior secondary school mathematics teachers’ professional self-esteem because of the noticeable negative behaviour of mathematics teacher at this level. The study also examined apart from the comparison between professional self-esteem of public and private mathematics teachers in junior secondary schools, the differential in professional self-esteem of urban and rural mathematics teachers. The study was anchored on social learning theory by Bandura, while survey design was adopted. Multistage sampling procedures was used. First, all junior secondary schools and mathematics teachers in Ibadan metropolis were enumerated. Schools were then stratified into public and private and also into urban and rural schools. Simple random technique was used to select 150 mathematics teachers from 50 junior secondary schools (Private - 49 and Public - 101). Mathematics Teachers Professional Self-Esteem Scale (r = 0.81) was used to collect data. The data gathering lasted four weeks by the investigator with the assistance of three research assistants. Data were analysed using frequency count, mean, standard deviation and sampled t-test at 0.05 level of significance. Qualitative data were content analysed after observing five sessions of focus group discussions with the 25.0% of selected teachers. The results revealed a significant mean difference between public (x = 41.35) and private (x = 29.27); urban (x = 25.41) and rural (x = 21.69); male (x = 6137) and female (x" = 49.53) professional self-esteem of mathematics teachers. The professional self-esteem was higher in term of public, urban, and male mathematics teachers. Mathematics teachers’ professional self-esteem should be sustained and strengthened through incentives, good reward system, marking allowances, teacher gender sensitivities, prompt and timely promotion as at when due.